Remarks on orthotropic elastic models applied to wood - Mascia, Nilson Tadeu; Lahr, Francisco Antônio Rocco (FapUNIFESP (SciELO), 2006)
Wood is generally considered an anisotropic material. In terms of engineering elastic models, wood is usually treated as an orthotropic material. This paper presents an analysis of two principal anisotropic elastic models that are usually applied to wood. The first one, the linear orthotropic model, where the material axes L (Longitudinal), R(radial) and T(tangential) are coincident with the Cartesian axes (x, y, z), is more accepted as wood elastic model. The other one, the cylindrical orthotropic model is more adequate of the growth caracteristics of wood but more mathematically complex to be adopted in practical terms. Specifically due to its importance in wood elastic parameters, this paper deals with the fiber orientation influence in these models through adequate transformation of coordinates. As a final result, some examples of the linear model, which show the variation of elastic moduli, i.e., Young's modulus and shear modulus, with fiber orientation are presented.
Keywords: Anisotropic material; Compression test; Fiber orientation; Orthotropic elastic models; Wood elastic constants; Anisotropy; Compression testing; Elastic moduli; Elasticity; Fiber reinforced materials; Mathematical models; Orthotropic material; Wood elastic parameters; Wood; Compression Tests; Elastic Strength; Mathematical Models; Wood Fibers; Wood Properties